H/D exchange mass spectrometry and statistical coupling analysis reveal a role for allostery in a ferredoxin-dependent bifurcating transhydrogenase catalytic cycle - Berry, Luke; Poudel, Saroj; Tokmina-Lukaszewska, Monika; Colman, Daniel R.; Nguyen, Diep M.N.; Schut, Gerrit J.; Adams, Michael W.W.; Peters, John W.; Boyd, Eric S.; Bothner, Brian (Biochimica et biophysica acta. General subjects, 2018)
Recent investigations into ferredoxin-dependent transhydrogenases, a class of enzymes responsible for electron transport, have highlighted the biological importance of flavin-based electron bifurcation (FBEB). FBEB generates biomolecules with very low reduction potential by coupling the oxidation of an electron donor with intermediate potential to the reduction of high and low potential molecules. Bifurcating systems can generate biomolecules with very low reduction potentials, such as reduced ferredoxin (Fd), from species such as NADPH. Metabolic systems that use bifurcation are more efficient and confer a competitive advantage for the organisms that harbor them. Structural models are now available for two NADH-dependent ferredoxin-NADP+ oxidoreductase (Nfn) complexes. These models, together with spectroscopic studies, have provided considerable insight into the catalytic process of FBEB. However, much about the mechanism and regulation of these multi-subunit proteins remains unclear. Using hydrogen/deuterium exchange mass spectrometry (HDX-MS) and statistical coupling analysis (SCA), we identified specific pathways of communication within the model FBEB system, Nfn from Pyrococus furiosus, under conditions at each step of the catalytic cycle. HDX-MS revealed evidence for allosteric coupling across protein subunits upon nucleotide and ferredoxin binding. SCA uncovered a network of co-evolving residues that can provide connectivity across the complex. Together, the HDX-MS and SCA data show that protein allostery occurs across the ensemble of iron‑sulfur cofactors and ligand binding sites using specific pathways that connect domains allowing them to function as dynamically coordinated units. •HDX-MS of Pf NfnI at different catalytic step demonstrates protein allostery•Statistical coupled pathways connect sites of electron transfer in a bifurcating transhydrogenase•Dynamically coordinated protein regions are associated with the Pf NfnI catalytic cycle.